Morphological Characteristics of Schistosoma mansoni PZQ-Resistant and -Susceptible Strains Are Different in Presence of Praziquantel - Pinto-Almeida, António; Mendes, Tiago; de Oliveira, Rosimeire Nunes; Corrêa, Sheila de Andrade Penteado; Allegretti, Silmara Marques; Belo, Silvana; Tomás, Ana; Anibal, Fernanda de Freitas; Carrilho, Emanuel; Afonso, Ana (Frontiers in Microbiology, 2016)
Schistosomiasis is one of the most common human parasitic diseases whose socioeconomic impact is only surpassed by malaria. Praziquantel (PZQ) is the only drug commercially available for the treatment of all schistosome species causing disease in humans. However, there has been stronger evidences of PZQ-resistance on Schistosoma mansoni and thus it is very important to study the phenotypic characteristics associated with it. The aim of this study was to evaluate morphological alterations in S. mansoni PZQ-resistant adult worms and eggs, by comparing a PZQ-resistant strain obtained under PZQ drug pressure with a PZQ-susceptible strain. For this, scanning electronic microscopy was used to assess tegumental responsiveness of both strains under PZQ exposure, and optical microscopy allowed the monitoring of worms and eggs in the presence of the drug. Those assays showed that PZQ-susceptible worms exposed to the drug had more severe tegumental damages than the resistant one, which had only minor alterations. Moreover, contrary to what occurred in the susceptible strain, resistant worms were viable after PZQ exposure and gradually regaining full motility after removal of the drug. Eggs from resistant strain parasites are considerably smaller than those from susceptible strain. Our results suggest that there might be a difference in the tegument composition of the resistant strain and that worms are less responsive to PZQ. Changes observed in egg morphology might imply alterations in the biology of schistosomes associated to PZQ-resistance, which could impact on transmission and pathology of the disease. Moreover, we propose a hypothetical scenario where there is a different egg tropism of the S. mansoni resistant strain. This study is the first comparing two strains that only differ in their resistance characteristics, which makes it a relevant step in the search for resistance determinants.